2014
DOI: 10.1159/000371653
|View full text |Cite|
|
Sign up to set email alerts
|

A Case of Post-Radiotherapy Gastritis: Radiation Does Not Explain Everything

Abstract: Hemorrhagic gastritis is a possible late toxicity outcome after radical radiotherapy but it is nowadays a very rare condition and most likely depends on other clinical factors. We report the case of a 77-year-old woman with a symptomatic solitary extramedullary intra-abdominal plasmacytoma and multiple gastric comorbidities, treated with external beam radiotherapy. Despite the good response to radiotherapy, the patient experienced multiple gastric bleeding a few months later, with the need of multiple treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In patients with radiation‐induced soft‐tissue necrosis, HBO‐induced neovascularization commonly reaches a plateau effect after approximately 20 treatments, consistent with the clinical improvement and cessation of gastrointestinal bleeding noted in our case after 25 treatments 7. HBOT is infrequently reported as a therapeutic option for RIHG 1,8,9. Banerjee et al1 reported an adult patient with refractory radiation‐induced gastritis who received 30 HBOT sessions, after which melena stopped, and the patient did not require further transfusion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In patients with radiation‐induced soft‐tissue necrosis, HBO‐induced neovascularization commonly reaches a plateau effect after approximately 20 treatments, consistent with the clinical improvement and cessation of gastrointestinal bleeding noted in our case after 25 treatments 7. HBOT is infrequently reported as a therapeutic option for RIHG 1,8,9. Banerjee et al1 reported an adult patient with refractory radiation‐induced gastritis who received 30 HBOT sessions, after which melena stopped, and the patient did not require further transfusion.…”
Section: Discussionsupporting
confidence: 84%
“…7 HBOT is infrequently reported as a therapeutic option for RIHG. 1 , 8 , 9 Banerjee et al 1 reported an adult patient with refractory radiation-induced gastritis who received 30 HBOT sessions, after which melena stopped, and the patient did not require further transfusion.…”
Section: Discussionmentioning
confidence: 99%